Penerapan Daya Paksa dalam Penyelesaian Perkara Penganiayaan yang dilakukan Korban Terhadap Pelaku Begal - Syauta, Eko Prasetio; Titahelu, Juanrico Alfaromona Sumarezs; Leasa, Elias Zadrach (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction:  Forced power in criminal law is the most important part and cannot be separated from criminal acts to measure and determine a grant of accountability to someone who commits a crime and is regulated in Article 48 of the Criminal Code which states: Whoever commits an act due to the influence of coercive force, is not can be punished. However, in the case that occurred at the Kepanjen District Court in Malang district, it gave the opposite decision regarding the abuse case committed by the victim MZA against the robber by giving MZA a guilty verdict for legally committing maltreatment which caused the death of a person as stipulated in Article 351 of the Criminal Code.Purposes of the Research: To find out and analyze the process of resolving cases of abuse committed by victims against robbers, to find out and analyze the judge's legal considerations regarding the criminal act of abuse committed by the victim against the robber.Methods of the Research:  The research method used is Normative Juridical, Type of research is Descriptive Analytical, Sources of legal materials: Primary, Secondary and Tertiary, Techniques for collecting legal materials using Literature Study, Analysis of legal materials using Qualitative methods.Results of the Research:  The results of the study show that: 1. Sanctions were given to MZA as the perpetrator of the persecution that caused the death of a person (in this case the victim of mugging) committed by the victim MISNAN and MAD (in this case the perpetrator of the robbery) in Decision Number 1/Pid.Sus- Anak/2020/PN.Kpn should not have been dropped on MZA because the act can be categorized as an act committed under coercive circumstances as stipulated in Article 48 of the Criminal Code. 2. Overall in Decision Number 1/Pid.Sus-Anak/2020/PN.Kpn the Panel of Judges has considered the existence of acts of self-defense in the case. However, according to the author, the Panel of Judges did not consider the legal facts at the location a case incident that forced and threatened MZA so that he could not escape which led to the act of taking out a knife and stabbing him as part of MZA's self-defense efforts